THE INTERVENTION CONTRACT RELAX HAMSTRING AND HOLD RELAX QUADRICEPS BETTER THAN CONTRACT RELAX HAMSTRING AND ISOTONIC EXERCISE QUADRICEPS IN IMPROVING FLEXIBILITY OF HAMSTRING ON WOMEN OF PKK AT BANJAR JAMBE BELODAN, DESA DAUH PEKEN, TABANAN - Megasari, Putu Santi Krishna; Andayani, Ni Luh Nopi; Purnawati, Susy; Wiryanthini, Ida Ayu Dewi (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i01.p05, 2018)
ABSTRACT Lack of physical activity to excessive physical activity, pregnancy and lack of exercise in women affects the hamstring muscle shortening if left unchecked will cause a loss of flexibility in the muscles. This study is an experimental research design with Two Group Pre and Post Test Design involving 22 samples were divided into 2 groups: treatment group 1 with intervention Contract relax hamstring and hold relax quadriceps and treatment group 2 with intervention Contract relax hamstring and Isotonic exercise quadriceps , Paired samples t-test showed the value of p = 0.000 in both groups. 22.82 (SB 7.85) cm in group 1 and 16.54 (SB 6.43) cm in group 2. The test results independent sample t-test showed the value of p = 0.000 on the difference increased flexibility of the hamstring muscles. The conclusion of this study is the contract hold-relax relax the hamstring and quadriceps better than contract relax the hamstring and quadriceps Isotonic exercise in improving the flexibility of the hamstring on Women of PKK in Banjar Jambe Belodan, Desa Dauh Peken, Tabanan. Keywords: hamstring tightness, flexibility of hamstring muscles, stretching, contract relax, hold relax, Isotonic exercise